Association of frailty with regional sagittal spinal alignment in the elderly. (February 2022) - Hong, Yun Gi; Kim, Hyung-Cheol; Jeon, Hyeongseok; An, Seong Bae; Lee, Ji Yeon; Lee, Jong Joo; Kim, Kwang Joon; Kim, Chang Oh; Shin, Dong Ah; Yi, Seong; Kim, Keung Nyun; Yoon, Do Heum; et al.
Highlights: The spinal degenerative changes gradually exacerbate the spinal alignment. Frailty could be an important factor that influences spinal alignment in the elderly. Frailty mainly affected lumbo-pelvic alignment, and consequently affected whole spine. Abstract: The degenerative changes in the spine of the frail elderly gradually exacerbate the alignment of the spine as the degeneration progresses. This study was conducted to assess the relationship between frailty and spine sagittal alignment measured in terms of global, cervical, thoracic, and lumbo-pelvic parameters. In total, 101 patients aged 75 years and older hospitalized for spine surgery were prospectively enrolled. We evaluated spinal sagittal parameters by dividing them into global (C7 sagittal vertical axis [SVA] and T1 pelvic angle [T1PA]), cervical (the C2-7 Cobb angle, Jackson line, and C2-7 plumb line), thoracic (thoracic kyphosis [TK]), and lumbo-pelvic (pelvic tilt [PT] and pelvic incidence minus lumbar lordosis value [PI-LL]). Patient characteristics; the Fatigue, Resistance, Ambulation, Illness, Loss of Weight (FRAIL) scale; and sagittal spinal parameters were included in the analysis. Multiple regression analysis was performed to identify associations between the FRAIL scale and sagittal spinal parameters. The FRAIL scale showed correlations with global sagittal parameters (C7 SVA [β = 0.225, p = 0.029] and T1PA [β = 0.273, p = 0.008]) and lumbo-pelvic parameters (PT [β = 0.294, p = 0.004] and PI-LL [β = 0.323, p = 0.001). Cervical and thoracic parameters were not directly associated with the FRAIL scale. LL and PI-LL were associated with TK, and TK was associated with cervical parameters (the C2-7 Cobb angle, Jackson line and C2-7 plumb line). In conclusion, frailty status could be an important factor that influences sagittal spinal alignment in the elderly. In this study, it was found that frailty mainly affected the balance of lumbo-pelvic alignment, and consequently affected the balance of the whole spine.